A PepT1 mediated medicinal nano-system for targeted delivery of cyclosporine A to alleviate acute severe ulcerative colitis. (13th August 2019) - Wu, Ya; Sun, Minghui; Wang, Dan; Li, Genyun; Huang, Jiangeng; Tan, Songwei; Bao, Lin; Li, Qian; Li, Gao; Si, Luqin
Abstract : A novel nano-system (PKMCN) with medical value could accumulate in the inflamed colon tissues and exhibit a strong anti-inflammatory effect. Abstract : To effectively alleviate acute severe ulcerative colitis (ASUC), we developed a colon-specific delivery system—PLGA–KPV/MMT/CS multifunctional medicinal nanoparticles loaded with cyclosporine A (CyA). The lysine–proline–valine (KPV) tripeptide, which possesses anti-inflammatory properties and high affinity to peptide transporter 1 (PepT1), can target therapy-related cells (colonic epithelial cells and macrophages) via overexpression of PepT1. Montmorillonite (MMT)/chitosan (CS) coating can reduce CyA leakage in the upper gastrointestinal tract (GIT) and enhance nanoparticle adhesion to the inflamed colon. The bio-distribution demonstrated that nanoparticles can specifically accumulate in the inflamed tissues and can be retained for up to 36 h. After being treated with the CyA–PLGA–KPV/MMT/CS nanoparticles (PKMCN), the mice with DSS-induced ulcerative colitis exhibited significant improvements in body weight, colon length, and disease activity index. Moreover, biochemistry and immunohistochemical analysis showed that the PKMCN treatment group performed as well as the healthy group. Intriguingly, PKMCN without CyA also presented marked therapeutic effects. Our results suggested that PKMCN could be a promising drug delivery system for ASUC therapy by targeting inflamed cells, prolonging curative time, and mitigating colitis.